Assessing the Sorptive Ability of Synthesized Graphene Oxide‐Metal Oxide Composite to Remove Certain Lanthanides. Issue 12 (25th October 2020) - Sheha, Reda R.; Mekawy, Zakaria A.; Someda, Hanan H.; Shehata, Mohamed K. K.; Mahmoud, Wagiha H.
Abstract: A metal oxide decorated graphene oxide composite (GO‐MO) is prepared via fixation of manganese dioxide (MnO2 ) on the surface of graphene oxide (GO). The composite is used as a sorbent for the separation of europium and cerium ions from aqueous solutions. The synthesized materials are characterized using scanning electron microscopy, thermogravimetric analysis, X‐ray diffraction, Raman spectroscopy, and Fourier transform infrared spectroscopy. The role of different variables on the sorptive ability of these materials is studied. Two simplified kinetic models, pseudo‐first order and pseudo‐second order, are applied to describe the kinetics of the sorption process. It is found that sorption of Eu(III) and Ce(III) ions on the synthesized sorbents could be described more favorably by the pseudo‐second‐order kinetic model. Sorption data are analyzed with Freundlich and Langmuir isotherm models. Desorption of europium and cerium ions from loaded sorbents is carried out using different eluents. Eu(III) ions are easily desorbed from loaded samples using 0.01 m EDTA while Ce(III) ions are easily eluted using 0.01 m AlCl3 . The obtained data clarify that the synthesized composite could be considered as a promising candidate for preconcentration and separation of some lanthanide elements from aqueous solutions. Abstract : A graphene oxide‐manganese dioxide composite is successfully synthesized. The physical properties of the composite are upgraded compared with its precursors. It has similar lamellar wrinkled structures that are crystalline in nature and chemically stable at pH >3. The composite is effectively applied in the removal of 152+154 Eu and 141 Ce radionuclides that sufficiently elutes using AlCl3 and EDTA eluents.